Pelatihan Self-Regulation, Assertiveness, Dan Time Management Dengan Kearifan Lokal Masyarakat Samin Untuk Meningkatkan Kemandirian Belajar - Rodiyah Rodiyah; Elfriska Auly Adenia (Universitas Islam Indonesia, 2022)
The covid-19 pandemic requires students to take Distance Learning (PJJ). So that demands to be able to adapt and have self-regulated learning. SAT (Self-Regulation, Assertiveness, and Time Management) training aims to increase the learning independence of students with a Samin cultural background. The subjects used were 14 junior high school students in Tanduran Hamlet, Kemantren Village, Kedungtuban District, Blora Regency. The method used is a quasi experiment with pre-experimental research design type one group pretest and posttest design. The measuring tool used is the scale of learning independence. The results of this study indicate that there is an increase in students' learning independence scores after participating in the SAT training with the local wisdom of the Samin community. SAT training with local wisdom of the Samin community is quite effective in increasing students' learning independence.